PENGARUH KOMPENSASI FINANSIAL TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS PENGELOLA KEUANGAN DAN ASSET DAERAH KABUPATEN ENREKANG - AM, Sanusi; Andika, Andika (Perpustakaan dan Penerbitan Unismuh Makassar, 2017)
The research was conducted at the Office of Financial Management and Regional Asset of Enrekang Regency, the research population is all employees of the Financial Management Service and as many as 80 employees while the sample size is determined using slovin method that is as much as 44 employees of the sample. Data were collected using observation, questionnaire, and documentation, while data analysis used validity test, reliability test, simple linear regression test, coefficient of determination, and hypothesis test using partial significance test (t test statistic). The result of data analysis shows that the variable of financial compensation with the performance of the officer at the Office of Financial Management and Regional Asset of Enrekang Regency, which is shown by validity test is greater than 0.300 (valid) rtabel, reliability test obtained Cronbach's Alpha value bigger than rtabel (Cronbach's Alpha 0,980> rtabel 0,297), simple linear regression test Y = -1,034 + 0,684 X (positive value), coefficient of determination 0,920, while for hypothesis test obtained tcount value bigger than ttable (t count 21,949> ttabel 2,018) at 5% significant level. The coefficient of determination obtained by 0.920 means that the financial compensation variable (X) gives the effect of 92% with the variable of employee performance (Y), while the rest is 8% is influenced by other variables not examined in the study.